Pengaruh Kepemimpinan Transformasional Kepala Madrasah Terhadap Kinerja Guru di Bustanul Athfal Aisyiyah Bajong Kecamatan Bukateja Kabupaten Purbalingga - Khotimah (LPPM IAINU Kebumen, 2020)
This research is based on the importance of teacher performance in the success of the learning process. In this regard, this study aims to determine the effect of the transformational leadership of the madrasa head on teacher performance at BA Aisyiyah Bajong, Bukateja District, Purbalingga Regency. This research is a correlational quantitative research. The population and sample in this study were all BA Aisyiyah Bajong teachers, Bukateja District, Purbalingga Regency, totaling 5 people. Data collection used a questionnaire, and data analysis used a simple regression analysis technique. This study concluded that the Madrasah Principal's Transformational Leadership has a significant influence on the performance of BA Aisyiyah Bajong Teachers, Bukateja District, Purbalingga Regency, as evidenced by the value of Sig = 0.011 < α = 0.05. The value of the correlation coefficient (r2) = 0.627 or a contribution of 62.7%.